Adoption of Self-Service Technology (SSTs) towards customer spending behaviour - Hor, Cindy; Kong, Jia Hui; Lay, Yi Cong; Tan, Kok An; Rathneswary, Sridhar (2020)
This research studies the relationship between perceived ease of use, perceived usefulness, technology compatibility, dining duration and consumer spending behaviour. The target respondents for this study is 400 people who have visited, still visiting or might visit the self-service technology-based restaurants in Malaysia. To execute this study, five statistic results were taken into account which were cronbach’s alpha, composite reliability, average variance extracted, discriminant validity as well as hypothesis testing. Furthermore, the Partial Least Squares Structural Equation Modelling (PLS-SEM) had been conducted in this study. The results show that there is an insignificant relationship between perceived ease of use, perceived usefulness, technology compatibility, dining duration and consumer spending behaviour. This study is providing a wide knowledge regarding the rising self-service technology-based restaurants in Malaysia and its benefits to the society such as restaurants consumers, restaurants owners, policy makers and also government of Malaysia